Developing a game-based learning assessment framework towards ubiquitous computational thinking among undergraduate students - Jonathan Hiew Yin Kin; Maizatul Hayati Mohamad Yatim; Tan Wee Hoe; Wong Yoke Seng (Pejabat Karang Mengarang UPSI, 2021)
This article discusses on a working study from a research on the usage of a game-based learning assessment framework as a standard guideline to assess undergraduate students' understanding and performance towards ubiquitous computational thinking properly. The objective of this research is to construct an appropriate game-based learning assessment framework to learn ubiquitous computational thinking and to determine the importance of the game-based learning approach. The methods in conducting this research study are a mixed method research with Delphi methodology approach. The game-based learning assessment framework was constructed based on results gathered by literature reviewing papers and afterward questionnaires as an online survey given to experts from game development and computer science fields by phases to answer and validate. The results gathered according to phases were performed using thematic analysis and descriptive statistics respectively. The expected results of this study are that the game-based learning assessment framework is able to assess undergraduate students' understanding and learning performance towards ubiquitous computational thinking and also able to align and incorporate into computing curriculum.